Factors driving the adoption of cooking banana processing and utilisation methods in Nigeria - Lemchi, J.; Tshiunza, M.; Onyeka, U.; Tenkouano, A. (2005)
As part of efforts in realising her aim of introducing cooking banana into Nigeria, the International Institute of Tropical Agriculture (IITA) mounted training and awareness campaigns on its utilisation in collaboration with Shell and Agip Oil companies between 1991 and 1997. This study looked into the adoption profile of the utilisation methods and the factors that may have influenced it. Data were collected from a random sample of 232 respondents from 24 villages in southeast Nigeria. Results showed an overall adoption level of 79.5%. The highest adoption levels were obtained for those utilisation methods similar to local and traditional methods of plantain consumption and lowest for non-traditional uses. The extent or intensity of adoption by the respondents ranged from 1 processing method to 7, with an average of 3. As a proportion of the number of utilisation methods on which training was given, the intensity of adoption ranged from 12.5% to 100% with a mean of 52.2%, meaning that the respondents have adopted more than 50% of the total number methods on which they received training. The major factors which have strongly influenced the adoption process were the level of educational attainment, social status, primary occupation, intensity of training received, availability of commercially-produced plantain products in the market/area, trialability as well as the number of desirable attributes of the utilisation methods.